Fundamentals of lighting - Winchip, Susan M (New York Fairchild Books, an imprint of Bloomsbury Publishing Inc, 2017)
"Fundamentals of Lighting, 3rd Edition, takes an integrated approach to the study of lighting and design. Topics include lighting system basics, lighting and the design process, human factors, sustainability, global issues, regulations, business practices, and the LEED building certification program"--
Machine generated contents note: -- Preface -- Part 1: Principles of Lighting -- 1. Introduction to Quality Lighting -- 2. Color and Directional Effects of Lighting -- 3. Natural and Electrical Light Sources -- 4. Energy, the Environment, and Sustainable Design -- 5. Illumination, Well-Being, and Behavior -- 6. Lighting Systems: Luminaires -- 7. Lighting Systems: Controls -- 8. Quantity of Light Part Two: Lighting Design Applications and the Design Process -- 9. Lighting Design Process: Project Planning through Design Development -- 10. Lighting Design Process: Contract Documents through Post-Occupancy Evaluation -- 11. Residential Applications -- 12. Commercial Applications Appendix A: Lighting Manufacturers, Distributors, and Suppliers -- Appendix B: Professional Organizations, Government Agencies, and Trade Associations -- Appendix C: References -- Appendix D: LEED Certification Credit Attributes Related to Quality Lighting -- Glossary -- Index
Includes index
2
Keywords: ARCHITECTURE / Interior Design / General; ARCHITECTURE / Interior Design / Lighting; Electric lighting; Lighting, Architectural and decorative; Lighting